2017
DOI: 10.1007/s12149-017-1166-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical symptoms and striatal DAT uptake in patients with DLB

Abstract: In patients with DLB, only parkinsonism is associated with a reduction in striatal DAT uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
3
18
1
Order By: Relevance
“…Three of the 30 pathologically confirmed DLB subjects however had normal DAT scans, but these patients were found to have minimal pathology in the brain stem (with predominantly neocortical or limbic Lewy bodies) and had presented with fluctuations and visual hallucinations,19 suggesting DLB patients with minimal brainstem Lewy bodies and therefore minimal parkinsonism maybe missed. Indeed, a negative correlation between the severity of parkinsonism and DAT uptake in the striatum has been reported in patients with DLB, with no correlation with the other core features of DLB 20. There were also three false-negative DAT scans in the recent postmortem study, from patients who had AD clinically at the time of their scan, but developed DLB symptoms in the years afterwards, suggesting Lewy body pathology was not present at the time of the scan, but may have developed later, leading to mixed AD/DLB ultimately 19…”
Section: Methodsmentioning
confidence: 99%
“…Three of the 30 pathologically confirmed DLB subjects however had normal DAT scans, but these patients were found to have minimal pathology in the brain stem (with predominantly neocortical or limbic Lewy bodies) and had presented with fluctuations and visual hallucinations,19 suggesting DLB patients with minimal brainstem Lewy bodies and therefore minimal parkinsonism maybe missed. Indeed, a negative correlation between the severity of parkinsonism and DAT uptake in the striatum has been reported in patients with DLB, with no correlation with the other core features of DLB 20. There were also three false-negative DAT scans in the recent postmortem study, from patients who had AD clinically at the time of their scan, but developed DLB symptoms in the years afterwards, suggesting Lewy body pathology was not present at the time of the scan, but may have developed later, leading to mixed AD/DLB ultimately 19…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the clinical differentiation of patients with AD from those with DLB may be diffi cult because of overlapping clinical and pathological features. 6 Conventional MR imaging shows focal volume loss classically starting in the entorhinal cortex, involving the medial temporal lobe and hippocampus, as well as the parietal lobe in AD. 51 NmMRI shows no reduction in signal intensity in the substantia nigra in AD, while a signal reduction in the substantia nigra is prominent in patients with PD and DLB.…”
Section: Imaging Findings Pdmentioning
confidence: 99%
“…51,52 Recent studies have indicated that MIBG myocardial scintigraphy provides diagnostic information that is useful for differentiating DLB from AD. 6 Moreover, the combination of DaTSCAN and MIBG myocardial scintigraphy may provide a powerful differential diagnostic tool when it is difficult to differentiate patients with DLB from those with AD using DaTSCAN or MIBG myocardial scintigraphy alone. 6 (Fig.…”
Section: Imaging Findings Pdmentioning
confidence: 99%
See 2 more Smart Citations